Potent benzoazepinone γ-secretase modulators with improved bioavailability. Issue 17 (1st September 2015) - Methot, Joey L.; Fischer, Christian; Li, Chaomin; Rivkin, Alexey; Ahearn, Sean P.; Brown, William Colby; Kattar, Sam; Kelley, Elizabeth; Mampreian, Dawn M.; Schell, Adam; Rosenau, Andrew; Zhou, Hua; et al.
Graphical abstract